The basics of coding a rehabilitation diagnosis in clinical practice for the physical therapist. - Romanyshyn M.J (Kharkov National Pedagogical University, 2012)
Directions of the use international classification of functioning are considered, limitations of vital functions and health in clinical activity of physical physical therapist. Bases for the construction of rehabilitation diagnosis in clinical practice are shown. The analysis of publications of Worldwide organization of health protection and World confederation of physical therapy is presented. The necessity of the use of foregoing classification for clinical practice of physical therapist is set. The constituents of clinical activity of physical therapist are selected.